Islam Dan Agama Lokal Dalam Arus Perubahan Sosial - Tendi, Tendi (IAIN Ponorogo, 2016)
Abstract: Agama Djawa Soenda (ADS)( Djawa Soenda religion) is one of the local beliefs that bases in Cigugur, Kuningan, West Java. Among three eras of leaderships that existed there, the leadership of Tedjabuana prince was the most unique one because ADS developed in three different periods: the Dutch colonial rule; the Japanese occupation; and the Indonesian independence. Social change in the period of Tedjabuana had made ADStrapped several times in the vortex of conflict with a number of Muslims. The conflict could end when the new ruler, who was close to Islam, pressed the ADS follower until their group dissolved. The method used in this study was historical method with a qualitative descriptive analysis through the sociological-anthropological perspective. In this study, data collection was done by collecting various kinds of information from some literatures, social and cultural data that were found in the research field through observation and interviews process to support the validity of the data that was successfully obtained. The results showed that the big challenges faced by ADS from 1939 to 1964 was the result of the fast social change that had influenced almost all aspects of community life, including the religious aspect. The social changes led ADS to a conflict that had made it development stagnant and even paralyzed.Â Ø§Ù„Ù…Ù„Ø®Øµ: ÙƒØ§Ù† Ø§Ø¹ØªÙ‚Ø§Ø¯ Ø¬Ø§ÙˆØ© ÙˆØ³ÙˆÙ†Ø¯Ø§ (Agama Djawa Soenda, ADS) Ù…Ù† Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯Ø§Øª Ø§Ù„Ù…ØÙ„ÙŠØ© Ø§Ù„Ù…ØªÙ…Ø±ÙƒØ²Ø© ÙÙŠ Ø¬ÙŠØºÙˆØºÙˆØ± ÙƒÙˆÙ†ÙŠÙ†Ø¬Ø§Ù† Ø¬Ø§ÙˆØ© Ø§Ù„ØºØ±Ø¨ÙŠØ©. ÙˆÙ…Ù† ÙØªØ±Ø§Øª Ø«Ù„Ø§Ø« Ø±Ø¦Ø§Ø³Ø§Øª ÙƒØ§Ù†Øª Ø±Ø¦Ø§Ø³Ø©Â Ø§Ù„Ù…Ù„Ùƒ ØªÙŠØ¬Ø§Ø¨ÙˆØ§Ù†Ø§ ÙƒØ§Ù†Øª Ø±Ø¦Ø§Ø³Ø© Ø®Ø§ØµØ© Ù…ØªÙ…ÙŠÙ‘Ø²Ø© Ù„Ø£Ù† ÙÙŠÙ‡Ø§ ØªØ·ÙˆÙ‘Ø± Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯ ÙÙŠ Ø«Ù„Ø§Ø« ÙØªØ±Ø§Øª Ù…Ø®ØªÙ„ÙØ© Ù‡ÙŠ ÙØªØ±Ø© Ø§Ù„Ø§Ø³ØªØ¹Ù…Ø§Ø± Ø§Ù„Ù‡ÙˆÙ„Ù†Ø¯Ù‰ØŒ ÙˆØ§Ù„Ø§Ø³ØªØ¹Ù…Ø§Ø± Ø§Ù„Ø¥Ù„ÙŠØ§Ø¨Ø§Ù†ÙŠ ÙˆÙØªØ±Ø©